1988
DOI: 10.3109/14017438809105937
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in hydatid cyst of the lung: A Report of 460 Cases

Abstract: A series of 460 surgically treated cases of hydatid cyst of the lung is presented. Radiologic preoperative diagnosis was made in 90% of the patients. Cystotomy with subsequent capitonnage was performed in 395 cases, wedge resection in 27, lobectomy in 15 and segmental resection in 23 cases. After careful hemostasis, two drains were placed in the thorax and the thoracic cavity was closed. There were three postoperative deaths (0.6%) and two recurrences of cyst (0.4%) during follow-up investigation for periods u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 12 publications
(3 reference statements)
0
16
0
2
Order By: Relevance
“…A review of 14 reports on 4255 patients with intrathoracic hydatidosis surgically treated, published in the recent decade (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997) and covering the period from the early 70's till now, revealed a perioperative mortality of 1.45% [1,2,5,[8][9][10][11][12][13][14][16][17][18]. The overall postoperative early and late morbidity ranged from near zero to 17% in 3433 patients [2,5,[8][9][10][12][13][14][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of 14 reports on 4255 patients with intrathoracic hydatidosis surgically treated, published in the recent decade (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997) and covering the period from the early 70's till now, revealed a perioperative mortality of 1.45% [1,2,5,[8][9][10][11][12][13][14][16][17][18]. The overall postoperative early and late morbidity ranged from near zero to 17% in 3433 patients [2,5,[8][9][10][12][13][14][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Our policy in the surgical management of pulmonary hydatid disease is the conservative surgery. It is followed by the vast majority of thoracic surgeons [1,3,5,[8][9][10][11][12][13][14][15], and is especially justified in children [16,17]. A review of the practice of nine centers in surgical management of pulmonary hydatid cysts revealed that radical resection is performed approximately in 20% of all surgical procedures [1,5,[8][9][10][11][12]14,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides information about the anatomic and pathologic condition of the cysts. CT scans are usually adequate in diagnosing lung cysts [7]. CT scans are more sensitive and accurate than US in localizing the liver cysts, and therefore are very useful in helping surgeons choose the site of the phrenotomy incision in the diaphragm [7].…”
Section: Discussionmentioning
confidence: 99%
“…The most valuable diagnostic tool for pulmonary hydatid disease is the chest X-ray. 2,54,56 Although various images can be seen on the chest radiograph, the typical appearance is a homogeneous spherical or oval opacity with sharp contours. Computed tomography can show small cysts not visible on a chest X-ray, 2,56,57 and also the signs of a ruptured hydatid cyst.…”
Section: Diagnosismentioning
confidence: 98%